Numerical Investigation of Indoor Particle Behaviors in Different Ventilation Scenarios - Xiaohong Hu; Mengmeng Zhang; Fengxian Fan (Aerosol and Air Quality Research)
Abstract Indoor PM10 has become a major environmental concern because of its negative impact on human health. In this study, an Eulerian–Lagrangian method has been employed to numerically investigate the behaviors of PM10 under two typical ventilation systems: the top air supply ventilation system and the sidewall air supply ventilation system. The research results show that while particle size has a negligible impact on the behaviors of PM2.5, it significantly affects the behaviors of PM2.5–10. Moreover, PM2.5 is more likely to escape than PM2.5–10, while the latter is easier to deposit. Compared to the ceiling and floor, the side walls exhibit a higher rate of deposition of submicron particles. When the top air supply ventilation is used instead of the sidewall air supply ventilation, the relative particle number concentration in the room is significantly lower. Increasing the ventilation rate leads to higher particle removal efficiency, however, this effect becomes very limited when the ventilation rate is high. Compared with the sidewall air supply ventilation, the top air supply ventilation yields a higher particle deposition rate, a lower particle escape rate and higher particle removal efficiency at a given ventilation rate and time. The research results indicate that the top air supply ventilation system could be a better choice to maintain a cleaner indoor air environment with less energy consumption, however, in this scenario, the re-suspension of deposited particles should be taken into consideration. The experimental data and the numerical results are in satisfactory agreement. Graphical Abstract